2019
DOI: 10.1007/s42250-019-00062-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl Cellulose as an Efficient Corrosion Inhibitor for Aluminium in Acidic Environments: Experimental and Theoretical Approach

Abstract: The adsorption and inhibition performance of hydroxypropyl cellulose (HPC) on aluminium corrosion in 0.5 M HCl and 2 M H 2 SO 4 were investigated at 30-65 °C using potentiodynamic polarization, gravimetric measurement and quantum chemical computation technique respectively. Potentiodynamic polarization results confirmed that HPC acted as a mixed-type inhibitor in both aggressive solutions with a more dominant anodic effect. Results of gravimetric measurement revealed that HPC displayed significant regulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Table 2 represents the collection of cellulose derivatives used as corrosion inhibitors [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199].…”
Section: Derivatization Of Cellulose Has Been Widely Reported However Carboxymethyl Cellulose (Cmc)mentioning
confidence: 99%
“…Table 2 represents the collection of cellulose derivatives used as corrosion inhibitors [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199].…”
Section: Derivatization Of Cellulose Has Been Widely Reported However Carboxymethyl Cellulose (Cmc)mentioning
confidence: 99%
“…The values of are tabulated in Table 4. The higher negative values of the standard free energy change of adsorption approve that adsorption of inhibitor's molecules is proceeding spontaneously; they are ranging from -39.55 to -37.07 KJ mol -1 , which signifies that the adsorption of HYD (iso) occurs via a combination of physical and chemical processes [58,59].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It was found that maximum protection efficiency was 90% at 0.4 g/L of drug concentration at 333 K and 3 h exposure time. Nwanonenyi et al [16] investigated the adsorption behavior and inhibition efficiency of hydroxypropyl cellulose on aluminium corrosion in 0.5 M HCl and 2 M H2SO4. Maximum inhibitor efficiency was 84.29% in HCl and 95.92% in H2SO4 at 30 ℃ and 5 g/L inhibitor concentration.…”
Section: Introductionmentioning
confidence: 99%